ChemInform Abstract: Asymmetric α‐Hydroxylation of a Lactone with Vinylogous Pyridone by Using a Guanidine—Urea Bifunctional Organocatalyst: Catalytic Enantioselective Synthesis of a Key Intermediate for (20S)‐Camptothecin Analogues. Issue 23 (10th June 2014) - Watanabe, Tatsuya; Odagi, Minami; Furukori, Kota; Nagasawa, Kazuo
Abstract Application of this method is demonstrated by the synthesis of (+)‐C20‐desethylbenzylcamptothecin (VIII).